Anglų kalbos leksemų Šiaurės Amerikos lietuvių kalboje interpretavimo klausimu - Pažūsis, Lionginas (Baltistica, 1969)
ON INTERPRETATION OF ENGLISH LEXEMES IN AMERICAN LITHUANIANAn attempt has been made to interpret (in broad terms) English lexemes imported into American Lithuanian by adult bilinguals. The actual treatment of the subject is preceded by an extended survey of a given language contact situation.In exploring the causes of their importation, English lexemes are treated not only as a manifestation of lexical interference, but the reasons which motivate any speaker to accept them in their vocabulary are also widely dealt with. The imported lexemes are mainly interpreted as subject to the interference of the phonic, as well as the grammatical, system of the recipient language. They usually occur as phonemically integrated loanwords. Most of them are also integrated with the recipient grammar. The cases when under certain circumstances American Lithuanians display an indifference as to the grammatical treatment of the transferred English lexemes are explained by the favourable paradigmatic and syntagmatic factors of the recipient language.
Keywords: anglų kalbos leksemos; Šiaurės Amerika; lietuvių